Survei Kekuatan Otot Lengan, Koordinasi Mata-Tangan dan Kemampuan Smash pada Peserta Ekstrakurikuler Bola Voli SMA Negeri 1 Bululawang - Fatih Prayoga; Agus Tomi; Dona Sandy Yudasmara (Universitas Palangka Raya, 2023)
The research problem that the researchers took was that there was still a lack of skills in volleyball smash skills for male extracurricular participants at SMAN 1 Bululawang. The research done for describe the level of arm muscle power, hand and eye coordination and smash ability. This study aims to look at the level of arm muscle power, hand-eye coordination and smash ability. This study used a quantitative descriptive research with a test survey method. The research sample was 15 participants with purposive sampling technique. The instrument used is a test, when carrying out test activities it is recorded and supplemented by documentation. The tests carried out included arm muscle power, hand and eye coordination and smash ability. From the research results, the participants overall arm muscle power had a percentage of 51% included in less category, then hand and eye coordination had a percentage of 28% included in very less category, while smash ability had percentage 64% included in the sufficient category. This research can be concluded that arm muscle strength is not significant to smash ability, eye-hand coordination is not significant to smash ability and arm muscle strength and eye-hand coordination have a significant relationship to smash ability.